Surface roughening and top opening of single crystalline TiO2 nanowires for enhanced photocatalytic activity. (15th October 2016) - Lai, Lu-Lu; Wen, Wei; Fu, Bo; Qian, Xin-Yue; Liu, Jia-Bin; Wu, Jin-Ming
Abstract: One dimensional (1D) single crystalline nanostructures facilitate electron transport and reduce the charge recombination; whilst nanotubular structure and a roughened surface provide more active sites as well as more opportunities for target molecules to reach the photocatalyst. As a result, TiO2 thin films with such a structural design can be anticipated to possess excellent photocatalytic activity. In this study, top opened nanowires with nanoprotrusions on the surface, which are hierarchical yet single crystalline as a whole, were synthesized by a simple acid treatment at 80 °C for 36 h of hydrothermally synthesized titanate nanowires, followed by a final calcination at 450 °C for 1 h. The hierarchical TiO2 films exhibited significantly enhanced efficiency when utilized to assist the photodegradation of rhodamine B and phenol in water under UV light illumination. Graphical abstract: Surface roughening and top opening of single-crystalline anatase TiO2 nanowires were achieved via a facile and low temperature acid treatment route, followed by a final calcination. The film exhibited significantly enhanced photocatalytic activity when compared with the arrays of hydrothermally synthesized anatase TiO2 nanowire and the anodization TiO2 nanotube. Highlights: Surface roughening and top opening of titanate nanowires in H2 SO4 solution Nanoprotrusions precipitated epitaxially along the single crystalline nanowires. Final calcination achieved single-crystalline-like anatase nanowires. Single-crystalline-like nanowires exhibited much improved photocatalytic activity.